A fast positioning method with altitude hypothesis for BDS receivers. Issue 353 (4th March 2017) - Jing, S.; Li, B.; Liu, W.; Sun, G.
Abstract : A fast positioning method with altitude hypothesis is proposed and described for BeiDou Navigation Satellite System (BDS) receivers to reduce time to first fix (TTFF). First, a rough user position can be estimated using pseudorange measurements of Geostationary Earth Orbit (GEO) satellites and altitude hypothesis, which is called coarse positioning. The altitude aiding can improve the poor geometry of the GEO constellation. In addition, we use an altitude hypothesis instead of accurate altitude information to avoid increasing external assistance. Second, the full pseudoranges of non-GEO satellites are constructed using rough position and fractional code-phase measurements. Finally, the receiver position is determined with all full pseudoranges. Furthermore, the residuals test is used to check positioning convergence to the correct solution. In the end, the validity of the fast positioning method is checked with B1 observation data from the international GNSS Monitoring & Assessment System (iGMAS).